How do nurses use the early warning score in their practice? A case study from an acute medical unit. Issue 7 (19th December 2018) - Foley, Claire; Dowling, Maura
Abstract: Aims and objectives: This study aimed to describe how nurses use the early warning score (EWS) in an acute medical ward and their compliance with the EWS and explore their views and experiences of the EWS. Background: early warning score systems have been implemented in response to upward trends in mortality rates. Nurses play a central role in the use of EWS systems. However, barriers to their use have been identified and include behavioural, cultural and organisational approaches to adherence. Improvement strategies including education and training and electronic devices have assisted in compliance with the system. Design: A holistic single descriptive case study design was used. Methods: Data triangulation was used including non‐participant observation, semi‐structured interviews with nurses and document analysis. Nurses were observed using EWS and were subsequently interviewed. Data analysis was guided by systematic text condensation (STC), an approach underpinned by Giorgi's phenomenological method, where meaning units and themes are identified. The study adhered to the consolidated criteria for reporting qualitative research (COREQ) guidelines. Results: Three themes with associated meaning units were found. Protocol Adherence vs. Clinical Judgement addresses nurses' knowledge, skill and experience and patient assessment. Parameter Adjustment and Escalation included parameters not being adjusted or reviewed, junior doctors not being authorised to set parameters and escalation. The final theme Culture highlighted a task‐driven approach and deficient communication processes. Conclusion: This study highlights the need for ongoing training, behavioural change and a cultural shift by healthcare professionals and organisations to ensure adherence with EWS escalation protocols. Relevance to clinical practice: Improvements in education and training into recognition, management and communication of a deteriorating patient are required. Also, a cultural shift is needed to improve compliance and adherence with EWS practice. The potential use of electronic data should be explored.